Mathematical modelling of unsteady contact melting - Muchatibaya, Gift (University of Cape Town, 2014)
Includes abstract. === Includes bibliographical references (leaves 115-122). === The work in this thesis deals with the heat transfer and fluid flow problem encountered in the analysis of an unsteady contact melting process. Chapters 2 and 3 deal with only the heat transfer problem without fluid flow. In Chapter 2 the pre-melting problem is treated. The focus is to obtain the best approximate analytical solution to be used in the melting phase where there are no known exact solutions. The approximate solutions are constructed using the heat balance integral method.